Contribution of the EnvZ/OmpR two-component system to growth, virulence and stress tolerance of colistin-resistant Aeromonas hydrophila - Xiao, Gang; Zheng, Xiaofeng; Li, Jiyun; Yang, Yang; Yang, Jie; Xiao, Ning; Liu, Junqi; Sun, Zhiliang (Frontiers in Microbiology, 2022)
Aeromonas hydrophila is an important zoonotic pathogen responsible for septicemia, diarrhea and gastroenteritis, and has attracted considerable attention. The EnvZ/OmpR two-component system (TCS) mediates environmental stress responses in gram-negative bacteria. We investigated the role of the TCS in A. hydrophila by comparing the characteristics of the parental (23-C-23), EnvZ/OmpR knockout (23-C-23: ΔEnvZ/OmpR), and complemented strains (23-C-23:CΔEnvZ/OmpR). Under non-stress conditions, the 23-C-23:ΔEnvZ/OmpR strain showed a significant decrease in growth rate compared to that of 23-C-23. Transcriptome and metabonomic analysis indicated that many metabolic pathways were remarkably affected in the ΔEnvZ/OmpR strain, including the TCA cycle and arginine biosynthesis. In addition, the virulence of the ΔEnvZ/OmpR strain was attenuated in a Kuming mouse model. The ΔEnvZ/OmpR strain exhibited notably reduced tolerance to environmental stresses, including high temperature, different pH conditions, oxidative stress and high osmotic stress. The downregulated expression of genes related to cell metabolism, motility, and virulence in the ΔEnvZ/OmpR mutant strain was further validated by real-time quantitative PCR. Consequently, our data suggest that the EnvZ/OmpR TCS is required for growth, motility, virulence, and stress response in A. hydrophila, which has significant implications in the development of novel antibacterial and vaccine therapies targeting EnvZ/OmpR for the prevention and control of A. hydrophila.